Sumantra Ghoshal on management : a force for good - Ghoshal, Sumantra (Financial Times Prentice Hall, 2006)
Sumantra Ghoshal on Management represents GhoshalÂ¿s twenty-year intellectual odyssey to challenge the underpinnings of management thought; to expose, rework and replace the foundation stones of management thinking. Exploring his key ideas, and reflecting his genius for collaboration along the way, this book shows how he had become a force for good in the world of management The first book to bring all the key Ghoshal writings together in one place. When a guru is well known and respected collected guru works sell extremely well. Ghoshal was perhaps the foremost management theorist in Europe, and has an army of personal and professional admirers. Today's leading lights in management and strategy provide context and commentary. Introduction by Julian Birkinshaw, discusses Goshal's work as a whole and its relevance to today's business environment. Published on the anniversary of GoshalÂ¿s death, this title will be timely and supported by a national PR campaign that is sure to grab attention. Goshal's works are well grounded in research but deeply applicable to the everyday working environment. AUDIENCE: Will sell well to academics and general business readers alike. Key audience categories: senior managers, consultants, academics and students. BENCHMARKS: The Essential Drucker, HarperCollins 2003. Maslow on Management, John Wiley 1998.